The Impact of Attractiveness, Facilities, and Service Quality on Visitor Satisfaction: A Case Study of XYZ Attraction - Kalimin, Evan Crysthiansen; brian, Reagan; Natalia, Dessy (Jurnal EMT KITA, 2026)
Visitor satisfaction is a crucial indicator in maintaining the sustainability and competitiveness of a destination amidst the intense competition within the oceanarium industry in the Greater Jakarta area. The urgency of this study is driven by 2025 review data, which indicates that a leading marine educational tourism destination in Jakarta holds the lowest rating compared to its main competitors, suggesting a significant gap in visitor satisfaction. The primary issues identified include a decline in visual appeal due to poor aquarium cleanliness, poorly maintained facilities, and low service quality resulting from the presence of unauthorized third parties and less responsive staff. This study aims to empirically analyze the influence of attraction, facilities, and service quality on visitor satisfaction at the destination. Utilizing a quantitative method with a survey approach involving 173 respondents, the data were analyzed using the PLS-SEM technique via the SmartPLS 4.0 application. The results demonstrate that all three independent variables have a positive and significant effect on visitor satisfaction. The facility variable was identified as the most dominant factor in shaping satisfaction with a path coefficient of 0.494, followed by service quality (0.312) and attraction (0.215). Overall, this research model explains 93.4% of the fluctuations in visitor satisfaction. These findings provide practical contributions for the management to prioritize facility revitalization, enhance service standards through staff training, and improve aquarium cleanliness to create a more memorable tourism experience and increase visitor loyalty.